2022
DOI: 10.3390/nu14163359
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Levels Explored in the Latvian Cohort of Patients with Basal Cell Carcinoma Linked to the Sonic Hedgehog and Vitamin D Binding Protein Cutaneous Tissue Indices

Abstract: Ultraviolet radiation is known as one of the major contributors to skin malignancies, including basal cell carcinoma (BCC), which is the most common type of skin cancer. It is a heterogeneous tumor, which presents with various types that are stratified into low- and high-risk tumors. Sunlight is important for overall health and vitamin D synthesis in the skin, whereas deviations from the optimal level of vitamin D are shown to be associated with the risk of the development of BCC. The accumulating evidence sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…The article by Dr. Moisejenko-Goluboviča and colleagues [1] discusses the relationship between vitamin D and basal cell carcinoma (BCC), the most common type of skin cancer, which is primarily caused by ultraviolet radiation. The study found that most BCC patients were deficient in vitamin D and that low vitamin D levels were associated with aggressive and recurrent BCC in susceptible male individuals.…”
mentioning
confidence: 99%
“…The article by Dr. Moisejenko-Goluboviča and colleagues [1] discusses the relationship between vitamin D and basal cell carcinoma (BCC), the most common type of skin cancer, which is primarily caused by ultraviolet radiation. The study found that most BCC patients were deficient in vitamin D and that low vitamin D levels were associated with aggressive and recurrent BCC in susceptible male individuals.…”
mentioning
confidence: 99%